Radioisotope 32P for Keloid Therapy: A Review - Rahman, Wira Y; Budiawan, Budiawan; Suseno, Heny (Indonesian Journal of Chemical Research, 2024)
Keloids are skin disorders resulting from an abnormal wound healing response, often leading to excessive scar tissue growth. Keloids can be itchy, painful, and aesthetically disturbing. Keloid therapy varies, but until now, there is no standard method that is effective due to different patient responses. Racial, environmental, and genetic variables influence keloids. Various therapeutic techniques, such as surgery, cryotherapy, corticosteroid injections, laser light, and radiotherapy, have been used to treat keloids, but each has advantages and disadvantages. However, these treatments have limitations, such as high recurrence rates and patient discomfort. The application of radioisotope therapy, specifically using 32P, has emerged as a promising alternative. Radioisotope 32P emits β-particles, effectively inhibiting keloid cell growth by causing DNA damage and reducing collagen production. Studies show that 32P therapy significantly reduces keloid size and recurrence rates while causing minimal patient discomfort. Although there are potential risks, such as damage to surrounding healthy tissue, 32P therapy provides a practical and non-invasive option for keloid management. However, more research is required to fully understand this method’s effectiveness, safety, and long-term impact on keloid therapy, optimize treatment protocols, and minimize side effects.